A map of enhancer regions in primary human neural progenitor cells using capture STARR-seq - Gaynor-Gillett, Sophia C.; Cheng, Lijun; Shi, Manman; Liu, Jason; Wang, Gaoyuan; Spector, Megan; Guo, Qiuyu; Qi, Le; Flaherty, Mary; Wall, Martha; Hwang, Ahyeon; Gu, Mengting; et al. (Genome Research, 2025)
Genome-wide association studies (GWASs) and expression analyses implicate noncoding regulatory regions as harboring risk factors for psychiatric disease, but functional characterization of these regions remains limited. Here, we perform capture STARR-sequencing of over 70,000 candidate regions to identify active enhancers in primary human neural progenitor cells (phNPCs). We select candidate regions by integrating data from NPCs, prefrontal cortex, developmental timepoints, and GWASs. Over 8000 regions demonstrate enhancer activity in the phNPCs, and we link these regions to over 2200 predicted target genes. These genes are involved in neuronal and psychiatric disease-associated pathways, including neuronal system, nervous system development, and developmental delay. We functionally validate a subset of these enhancers using mutation STARR-sequencing and CRISPR deletions, demonstrating the effects of genetic variation on enhancer activity and enhancer deletion on gene expression. Overall, we identify thousands of highly active enhancers and functionally validated a subset of these enhancers, improving our understanding of regulatory networks underlying brain function and disease.